Heart Failure in Lebanon: A Review of the Literature - Hiba Deek; Angela Massouh; Patricia M Davidson (Jurnal Keperawatan Indonesia, 2022)
This research aimed to provide a comprehensive overview of the current literature on heart failure (HF) management in Lebanon and identify the implications for policy, practice, education, and research. The design of this research was a systematic review following preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Databases were searched using the search terms “heart failure” and “Lebanon” and associated MeSH terms. The abstracts of the selected articles were examined independently by two researchers; the sample characteristics, HF indices, and results of the included studies were extracted. Key findings and trends were synthesized. Eleven papers were reviewed with 2,774 participants (mean age = 57.98, SD = 13.09 years, and the majority [n = 1,494, 53.85%] were male). Over one-third reported having coronary artery disease, and half had hypertension. The mean ejection fraction was 47.28% (SD = 10.44), and the mean length of hospital stay was 7.97 days (SD = 10.28). Self-care was a common theme showing varying but low scores, especially in the self-management subscale. The findings of this study outline the unique characteristics of the population with HF in a Middle Eastern country. These characteristics should be considered when planning interventions in countries facing geopolitical instability in the context of population aging and the rise of noncommunicable diseases.   Abstrak Tinjauan Pustaka tentang Gagal Jantung di Lebanon. Penelitian ini bertujuan untuk menyajikan rangkuman kajian pustaka terkait manajemen gagal jantung di Lebanon dan mengidentifikasi implikasinya terhadap kebijakan, praktik, pendidikan, dan riset di bidang tersebut. Metode tinjauan sistematis digunakan pada penelitian ini dengan mengacu pada preferred reporting items for systematic reviews and meta-analyses (PRISMA). Beberapa istilah, seperti “gagal jantung” dan “Lebanon” serta istilah dalam medical subject headings (MeHS) lainnya digunakan dalam pencarian pada basis data. Kumpulan abstrak terpilih ditinjau dan diteliti dalam hal: karakteristik sampelnya, indeks gagal jantung, dan hasil penelitiannya. Poin utama temuan dan tren dipadukan. Pada sebelas manuskrip yang telah ditelaah, terdapat 2.774 partisipan (rerata umur = 57,98, SD = 13,09 tahun, dan mayoritas partisipan adalah laki-laki (n = 1.494, 53,85%). Lebih dari sepertiganya mengalami jantung coroner dan setengahnya mengalami hipertensi. Nilai mean untuk pecahan ejeksi sebesar 47,28% (SD = 10,44), dan nilai mean untuk lama rawat inap yang dijalani ialah 7,97 hari (SD = 10,28). Perawatan mandiri adalah tema yang paling sering muncul tetapi dengan variasi skor rendah, khususnya pada subskala manajemen mandiri. Temuan pada penelitian ini menggarisbawahi karakteristik unik pada populasi gagal jantung di negara-negara Timur Tengah. Karakteristik ini diharapkan dapat menjadi acuan dalam merencanakan intervensi pada negara yang menghadapi ketidakstabilan geopolitik, khususnya dalam konteks populasi lansia dan meningkatnya kasus penyakit tidak menular. Kata Kunci: gagal jantung, keperawatan, Lebanon, literasi, MENA region, perawatan mandiri